Learning Innovation of " Linking Karmina" with Contextual Approach and Role Playing - Salamah, Umi; Rokhyanto, Rokhyanto; Sumarti, Endang; Suyoto, Suyoto (International Journal of Educational Narratives, 2023)
Background. Karmina is one type of pantun of Indonesian intangible cultural heritage that is important to preserve. Purpose. This research aims to develop an innovation in flash pantun learning (Karmina) with a contextual approach and role-playing method at the Madrasah Ibtidaiyah and Elementary School levels in accordance with the independent learning platform. Method. This research uses a qualitative approach and the Borg & Gall development method. Data collection techniques used tests, observations, and interviews, while data analysis techniques used a flow analysis model. Data validity was done by triangulation technique. The data sources were students and teachers of elementary schools and madrasah Ibtidaiyah. The research locations are in Malang and Tulungagung. Results. The results of data analysis show (1) with a contextual approach, 100% of learners can make the cover and content of vocabulary used in daily conversation; (2) with the role playing method, Karmina linking learning is 100% complete, because learners can turn dialog into Karmina linking when playing roles; and (3) the Karmina linking learning model using a contextual approach and role playing method makes the learning atmosphere active, dynamic, fun, and meaningful. Conclusion. With these findings, it is suggested that Elementary School and Madrasah Ibtidaiyah teachers can use these findings for pantun learning to make it fun and meaningful for students, so that the nation's cultural heritage as a whole can be preserved.